Menuju Kecerdasan Buatan yang Non-Diskriminatif dalam Layanan Kesehatan: Memastikan Akses dan Pemanfaatan yang Setara bagi Wilayah Perdesaan dan Tertinggal - Ris Heskiel Najogi Sitinjak; Silvi May Angelia Purba; Salma Majidah; Natasya Anggraeni Azis (Jurnal HAM, 2025)
The enjoyment of the highest attainable standard of health is one of the fundamental human rights. Artificial Intelligence (AI) is a ground-breaking innovation with huge potential to accelerate multisectoral progress, including in healthcare. Yet, its reliance on data availability, governance structures, infrastructure, and technical expertise can perpetuate biases against underrepresented communities and exacerbate existing inequalities. This paper explores strategies to develop a just, inclusive, and humane AI framework that enhances healthcare services while ensuring equal access and utilization for people in rural and underdeveloped areas (RUAs). A narrative review was conducted through targeted searches in scientific databases and verified sources from April to June 2024 using relevant keywords such as “health as a human right,” “AI and health,” “AI in rural areas,” “AI and inequality,” “rural development,” and “AI and social determinants of health,”. The review highlights the profound impact of AI on RUA residents, who are disproportionately marginalized by the interplay of spatial and socioeconomic limitations. These challenges are amplified by uneven technological progress and the demand for specialized skills across different regions. Health data equity for RUAs could be enhanced by promoting social innovation, together with active community participation and human capital development. In this context, targeted training initiatives and coordinated efforts among educational institutions, employers, healthcare facilities, and labor unions can empower workers in RUAs to engage with evolving AI-driven systems. Ultimately, ideal and unbiased AI should safeguard health as a human right by ensuring inclusivity and non-discriminatory frameworks, becoming sustainable in its respective communities, and upholding ethical conduct.